Teachers' use of L1 in ESL classroom / Muhd Syahir Abdul Rani - Abdul Rani, Muhd Syahir (2013)
This study is a quantitative survey on the use of the first language (LI) in English classroom. The focus of the study is to seek information on this issue based on 3 main aspects namely 1) the teachers' attitude towards the use of LI in ESL classroom, 2) the teachers' beliefs towards the practicality of LI in ESL classrooms, and 3) the teachers' practise of LI in ESL classrooms. Besides that, this study also intended to find relationship between these 3 variables. The respondents of this study consisted of 109 English teachers from 15 schools in Selangor. The teachers were asked to complete a questionnaire to provide information for this study. The result of this study has shown that teachers had neutral attitudes towards the use of LI, and also had neutral beliefs towards the practicality of LI. The participants of this study also claimed that they rarely practiced the use of LI in their English class. The result also indicated that there is a very strong and significant relationship between teachers' attitudes towards the use of LI in ESL classroom and teachers' beliefs towards the practicality of LI in ESL classroom. Besides that, Pearson Correlation Test also revealed that there is a very strong and significant relationship between teachers' beliefs towards the use of LI in ESL classroom and teachers' practice of LI in ESL classroom.